PENGEMBANGAN METODE IN SILICO UNTUK KAJIAN AWAL KEAMANAN BAHAN TAMBAHAN PANGAN PADA RESEPTOR SEROTONIN - Hikmah, Bill
Nowadays the new potential compounds to be applied as food additives has been developed rapidly. These compounds must be safe to be consumed and may not cause any physiological changes in the body. A rapid test method was developed to meet these needs which involving interaction study between food additive compounds and receptors in the body. The receptor selected in the study was serotonin receptor, one of the crucial receptors in the body involves in various physiological functions such as in the cardiovascular and gastrointestinal systems. This study was conducted by developing an in silico method by docking and molecular dynamics simulations of food additive compounds of different functional classes (flavoring agents, antioxidants, sweetener, preservatives, and food coloring agents) against the 5-HT2B receptor (PDB ID: 5TVN), in which drugs with known affinity and effectivity againts the receptor were used as the references. Based on docking simulation results, the compounds were clustered and the top five compounds from each category were selected for the molecular dynamics simulation. Three parameters were used to evaluate the safety of food additives: the binding side, the threshold value of Ki (1.147 x 10- 3 nM), and the key amino acids VAL136, MET218, PHE340, PHE341, and ASN344. The results obtained from evaluation were compared to the data published by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). Eighteen compounds were predicted to be potentially safe, while seven others were predicted to be potentially unsafe. Based on these results, this developed method can be used as preliminary safety evaluation for novel food additive substances based on their interaction against serotonin receptor.